ANALISIS KELAYAKAN TARIF ANGKUTAN UMUM (SUPERBEN) DI KABUPATEN ROKAN HULU - Khairul Fahmi (Universitas Pasir Pengaraian, 2014)
Public transport tariff by the Government must consider two conflicting sides of the implementationof the public transport. For users who use public transport to facilities meeting the needs of the derivativewith a cheaper rate expectations. The other hand, as a provider of freight services provider for-profit. Thisstudy aims to know patterns public transport fares (superben) current. To evaluating public transit tariff(superben), toevaluating public transport fares applicable to consider the public transport operators , aswell as to evaluate the ability of passengers to pay and perceptions about public transport fares (superben)applies .